Nb2O5 (at) C material, preparation method thereof and application of Nb2O5 (at) C material in sodium ion micro capacitor
By combining niobium pentoxide and carbon material, Nb2O5@C material with excellent electrochemical performance was prepared, which solved the problem of poor electrochemical performance of Nb2O5 material, achieved high specific capacity, magnification and long cycle stability, and was suitable for sodium ion microcapacitors.
Patent Information
- Application Number
- CN202311212130.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-18
- Publication Date
- 2025-03-18
AI Technical Summary
The electrochemical performance of Nb2O5 materials is poor, resulting in poor magnification and cycling performance, making it difficult to meet the needs of sodium ion microcapacitors.
By combining niobium pentoxide material with carbon material, Nb2O5@C material with three-dimensional porous structure and flower cluster-like micromorphology was prepared. The surface of the nanosheets of this material is evenly coated with carbon, and the morphology and structure of the material are regulated through nanodesign to improve its electrochemical properties.
The Nb2O5@C material exhibits excellent specific capacity, magnification and cycling performance. The first discharge specific capacity can reach 245mAh/g, which can meet the needs of sodium ion capacitors and exhibit a capacitance retention rate of 75% in long cycle tests.
Smart Images

Figure CN119650309A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrical materials, and in particular relates to a Nb2O5@C material and a preparation method thereof, and an application in a sodium ion microcapacitor. Background Art
[0002] With the booming development of various emerging wearable and portable electronic products such as foldable smartphones, shapeable health monitors, and wearable sensors, flexible and miniaturized energy storage systems with excellent energy and power density and long life are required. Sodium-ion microcapacitors (NIMSCs) are considered to be a highly competitive class of next-generation miniaturized energy storage devices due to their abundant sodium resources and low cost. Orthorhombic niobium pentoxide (T-Nb2O5) has high chemical stability and open structure, and has the characteristics of "intercalation pseudocapacitance", and is considered to be an ideal high-rate sodium-ion anode material. However, Nb2O5 has inherent poor electronic conductivity and sluggish reaction kinetics, resulting in poor rate capability and cycling performance. Although most modification strategies are through combining with highly conductive carbon, their composite structures are different, which is far from the excellent rate capability and ultra-long cycling stability of NIMSCs. How to quickly prepare Nb2O5 with ideal structure and high electrochemical activity remains a major challenge. Summary of the invention
[0003] In view of this, the present invention provides a Nb2O5@C material and a preparation method and application in sodium ion microcapacitors, the main purpose of which is to solve the technical problem of poor electrochemical performance of Nb2O5 materials.
[0004] On the one hand, the present invention provides a Nb2O5@C material, wherein the Nb2O5@C is composited by a niobium pentoxide material and a carbon material; the Nb2O5@C material has a three-dimensional porous structure;
[0005] The microscopic morphology of the Nb2O5@C material is in the shape of a flower cluster, and a single three-dimensional flower-like structure is composed of multiple cross-layered nanosheets;
[0006] The carbon material is coated on the surface of the nanosheet.
[0007] Optionally, the particle size of the single three-dimensional flower-shaped structure is 1 to 5 μm.
[0008] Optionally, the thickness of the nanosheet is 10 to 50 nm.
[0009] Optionally, the thickness of the coated carbon layer is 2-4 μm.
[0010] Optionally, the particle size of the single three-dimensional flower-shaped structure is selected from any value of 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, or any range between the two.
[0011] Optionally, the thickness of the nanosheet is selected from any value of 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, or any range therebetween.
[0012] Optionally, the thickness of the coated carbon layer is selected from any value of 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, or any range between the two values.
[0013] The flower cluster structure in the present invention is composed of a plurality of flower-like structures, and a single flower-like structure is composed of a plurality of vertically crossed nanosheets stacked in layers, and carbon is uniformly coated on the surface of the nanosheets.
[0014] The flower-shaped Nb2O5@C material of the present invention has uniform morphology, high crystallinity, and exhibits excellent specific capacity, rate and cycle performance, so that the material has high use value and can meet the needs of sodium ion capacitors.
[0015] In a second aspect, the present invention provides a method for preparing the above-mentioned Nb2O5@C material, the preparation method comprising the following steps:
[0016] S1: a solution I containing a niobium source is heated under closed conditions to react I to obtain an intermediate I;
[0017] S2: mixing the intermediate I in step S1 with a carbon source to obtain an intermediate II;
[0018] S3: After the intermediate II in step S2 is subjected to heat treatment II in an inactive atmosphere, the Nb2O5@C material is obtained.
[0019] Optionally, in step S1, the heating reaction I is a solvent thermal reaction.
[0020] Optionally, in step S1, the niobium source and the solvent are mixed and stirred for 0.5 to 2 hours to obtain the solution I, and the pH of the solution I is neutral.
[0021] Optionally, in step S1, the mixing and stirring time of the niobium source and the solvent is selected from any value of 0.5, 1, 1.5, 2 hours or any range between the two.
[0022] Optionally, the pH of the solution I is adjusted to neutral with ammonium hydroxide.
[0023] Optionally, the ammonium hydroxide and the solution I are mixed and stirred at room temperature to adjust the pH to neutral; the stirring time is 10 to 30 minutes.
[0024] Optionally, the stirring time is selected from any value of 10 min, 15 min, 20 min, 25 min, 30 min, or a range between any two of them.
[0025] Optionally, in step S1, the temperature of the heating reaction I is 150-200° C., and the time of the heating reaction I is 20-24 hours.
[0026] Optionally, the temperature of the heating reaction I is selected from any value of 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, or a range between any two of them; the time of the heating reaction I is selected from any value of 20h, 21h, 22h, 23h, 24h, or a range between any two of them.
[0027] Optionally, in step S2, the intermediate I and the carbon source are mixed at room temperature and stirred for 5 to 10 hours to obtain intermediate II.
[0028] Optionally, in step S2, the stirring time is selected from any value of 5h, 6h, 7h, 8h, 9h, 10h or any range between them.
[0029] Optionally, in step S3, the temperature of the heat treatment II is 500-800° C., and the time of the heat treatment II is 3-10 hours.
[0030] Optionally, the temperature of the heat treatment II is selected from any value of 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, or a range between any two of them; the time of the heat treatment II is selected from any value of 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, or a range between any two of them.
[0031] Optionally, the niobium source is selected from hydrated niobium oxalate or niobium chloride.
[0032] Optionally, the carbon source is selected from dopamine, glucose or sodium alginate.
[0033] The niobium source and carbon source of the present invention can also be selected from other types in the prior art according to actual needs.
[0034] Optionally, the molar ratio of the niobium source to the carbon source is 0.8-1.2:0.8-1.2; wherein the molar number of the niobium source is calculated based on the molar number of niobium element in the niobium source, and the molar number of the carbon source is calculated based on the molar number of carbon element in the carbon source.
[0035] Optionally, the molar ratio of the niobium source to the carbon source is 0.9-1.2:0.9-1.2; further, the molar ratio of the two is 1.0-1.2:1.0-1.2; further, the molar ratio of the two is 1.0-1.1:1.0-1.1; preferably, the molar ratio of the two is 1:1.
[0036] Optionally, in step S1, the solvent is a mixture of water and ethylene glycol in a volume ratio of 1 to 3; further, the volume ratio of the two is 1.5 to 2.
[0037] Optionally, in step S3, the inert atmosphere is selected from nitrogen and / or argon.
[0038] The present invention can also select other inactive atmospheres according to actual needs.
[0039] In a third aspect, the present invention provides the use of the above-mentioned Nb2O5@C material as a negative electrode material in a sodium ion microcapacitor.
[0040] In a fourth aspect, the present invention provides a negative electrode material for a sodium ion microcapacitor, the negative electrode material comprising the above-mentioned Nb2O5@C material; wherein the content of the Nb2O5@C in the negative electrode material is 50 to 90 wt%.
[0041] Optionally, the content of Nb2O5@C in the negative electrode material is selected from any value of 50wt%, 60wt%, 70wt%, 80wt%, 90wt% or any range between the two.
[0042] Optionally, the negative electrode material further includes a conductive agent and a binder, the conductive agent includes conductive carbon black, and the binder includes polyvinylidene fluoride.
[0043] In a fifth aspect, the present invention provides a micro capacitor comprising the above-mentioned Nb2O5@C negative electrode; the micro capacitor is a planar interdigitated Nb2O5@C / / AC-NIMSCs.
[0044] The Nb2O5@C / / AC-NIMSCs of the present invention have a high 2 High surface energy density and excellent long cycle performance (at 300μA / cm 2 After 8000 cycles at the same current density, the capacitance retention rate was 75%).
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] (1) The flower-shaped Nb2O5@C negative electrode material prepared by nano-design regulation in the present invention has uniform morphology and high crystallinity.
[0047] (2) The Nb2O5@C negative electrode material obtained by the present invention has excellent electrochemical properties and a specific capacity of up to 245 mAh / g, which makes the material have high use value and can meet the needs of sodium ion capacitors. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 is the X-ray powder diffraction XRD pattern of the sample in Example 1 of the present invention;
[0049] Figure 2 The SEM image of the sample in Example 1 of the present invention is shown in FIG.
[0050] Figure 3 is the transmission electron diffraction TEM spectrum of the sample in Example 1 of the present invention;
[0051] Figure 4 This is a charge and discharge curve diagram of the sample in Example 1 of the present invention. DETAILED DESCRIPTION
[0052] The present application is further described below in conjunction with specific embodiments. The following are only a few embodiments of the present application, and are not intended to limit the present application in any form. Although the present application discloses the following preferred embodiments, they are not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the above disclosed technical content to make some changes or modifications are equivalent to equivalent implementation cases and are within the scope of the technical solution.
[0053] Unless otherwise specified, the raw materials in the examples of the present application were purchased from commercial sources and used directly without any special treatment.
[0054] Unless otherwise specified, the analysis methods in the examples all adopt conventional settings and conventional analysis methods of instruments or equipment.
[0055] In the examples of the present application, an X-ray powder diffractometer was used to observe the structure of the sample, and a scanning electron microscope was used to observe the morphology of the sample.
[0056] Instruments: scanning electron microscope (JSM-7900F), transmission electron microscope (JEM-2100), X-ray powder diffractometer (SmartLab), blue electric tester (LAND CT2001A).
[0057] The method of the flower-shaped Nb2O5@C negative electrode material of the present invention specifically comprises the following steps:
[0058] (1) Mixing the raw material containing the niobium source with water and ethylene glycol, and stirring with a magnetic stirrer for 1-1.5 hours;
[0059] (2) adding ammonium hydroxide to the transparent solution obtained in step (1) to adjust the pH to neutral, and stirring magnetically for half an hour;
[0060] (3) subjecting the mixed solution obtained in step (2) to a solvothermal reaction at 150-200° C. for 20-24 h; dispersing the hydrothermal product in a solution containing a carbon source, and magnetically stirring at room temperature for 5-10 h to obtain a carbon source-coated precursor;
[0061] (4) The carbon source-coated precursor obtained in step (3) is annealed at 500-800° C. for 3-10 h in an argon atmosphere, and naturally cooled to room temperature to obtain flower-shaped Nb2O5@C.
[0062] Charge and discharge test system:
[0063] The electrochemical test instrument used in this experiment is the LAND CT2001A
[0064] Charge and discharge test method:
[0065] This experiment adopts the rate charge and discharge test method, and the test is carried out at a current density of 0.25~20C, where 1C = 200mAg -1 .
[0066] Example 1 (Nb2O5@C)
[0067] Hydrated niobium oxalate and dopamine are used as initial raw materials.
[0068] First, 30 mL of ethylene glycol and 50 mL of water were mixed, and 0.538 g of hydrated niobium oxalate was dispersed in the mixture and magnetically stirred for 1 hour. Then 0.4 mL of ammonium hydroxide was added to adjust the pH to neutral, and then transferred to a 100 mL reactor and reacted at 180°C for 24 hours. The obtained product was centrifuged and washed three times with water and ethanol, respectively, at a centrifugal speed of 3000 rpm, and each centrifugal time was 6 minutes, and then vacuum dried at 80°C for 10 hours to obtain Nb2O5 powder.
[0069] 30 mg dopamine and 40 mg tris(hydroxymethyl)aminomethane) were weighed and dissolved in 50 mL water, 60 mg Nb2O5 powder was dispersed in dopamine buffer and stirred for 6 h to obtain a dopamine-coated precursor. The precursor was annealed at 650 °C (heating rate of 5 °C / min) in an argon atmosphere in a tube furnace for 8 h, and naturally cooled to room temperature to obtain flower-like Nb2O5@C, which was recorded as sample 1.
[0070] Figure 1 The X-ray diffraction pattern shows that the obtained product is Nb2O5@C, without other impurities and with high crystallinity.
[0071] from Figure 2Scanning electron microscopy revealed that Nb2O5@C is a nanoflower (particle size 3μm) assembled from ultrathin nanosheets (thickness 30nm).
[0072] Figure 3 This is the transmission diffraction pattern of Nb2O5@C, and its structure is clearly visible.
[0073] Figure 4 Nb2O5@C was charged and discharged at a current density of 0.25C, and the first discharge specific capacity was 245mAh / g.
[0074] Example 2 (Nb2O5@C)
[0075] Niobium pentachloride and dopamine are used as initial raw materials.
[0076] First, 0.55 g of niobium pentachloride was weighed and dispersed in 60 mL of ethylene glycol and 20 mL of water, transferred to a 100 mL reactor, and reacted at 180°C for 24 hours. The product obtained after hydrothermal treatment was centrifuged and washed three times with water and ethanol, respectively, at a centrifugal speed of 5000 rpm, each centrifugal time of 5 minutes, and then dried in a vacuum drying oven at 80°C for 12 hours to obtain Nb2O5 powder.
[0077] Weigh 50 mg dopamine and dissolve it in 80 mL water, weigh 80 mg Nb2O5 powder and add it to the dopamine solution, stir at room temperature for 6 h to obtain the precursor. Anneal the precursor at 500 °C (heating rate of 3 °C / min) in an argon atmosphere in a tube furnace for 8 h, and cool it naturally to room temperature to obtain flower-like Nb2O5@C.
[0078] The test showed that the first discharge specific capacity of the sample at a current density of 0.25C was 192 mAh / g.
[0079] Example 3 (Nb2O5@C)
[0080] Hydrated niobium oxalate and sodium alginate are used as initial raw materials.
[0081] First, 40 mL of ethylene glycol and 40 mL of water were mixed, 0.807 g of hydrated niobium oxalate was weighed and dispersed in the mixture, magnetically stirred for 70 min, and then ammonium hydroxide was added to adjust the pH to neutral, and then transferred to a 100 mL reactor and reacted at 160 ° C for 24 h. The obtained product was centrifuged and washed three times with water and ethanol, respectively, at a centrifugal speed of 5000 rpm, and each centrifugal time was 5 minutes, and then vacuum dried at 80 ° C for 10 h to obtain Nb2O5 powder.
[0082] Weigh 0.75g sodium alginate and dissolve it in 50mL water, disperse 0.45g Nb2O5 powder in the sodium alginate solution, and stir magnetically at room temperature for 10h to obtain a sodium alginate-coated niobium pentoxide precursor. Anneal the precursor at 700℃ (heating rate of 8℃ / min) in an argon atmosphere in a tube furnace for 7h, and cool it naturally to room temperature to obtain flower-shaped Nb2O5@C.
[0083] The test showed that the first discharge capacity of the sample at a current density of 0.25C was 175 mAh / g.
[0084] Example 4 (Nb2O5@C)
[0085] Niobium pentachloride and glucose are used as initial raw materials.
[0086] First, 1.53 g of niobium pentachloride was weighed and dispersed in 45 mL of ethylene glycol and 35 mL of water, transferred to a 100 mL reactor, and reacted at 170°C for 24 hours. The product obtained after hydrothermal treatment was centrifuged and washed three times with water and ethanol, respectively, at a centrifugal speed of 6000 rpm, each centrifugal time of 7 minutes, and then dried in a vacuum drying oven at 80°C for 8 hours to obtain Nb2O5 powder.
[0087] Weigh 200 mg of glucose and dissolve it in 100 mL of water, weigh 100 mg of Nb2O5 powder and add it to the glucose solution, stir at room temperature for 10 h to obtain the precursor. Anneal the precursor at 750 °C (heating rate of 10 °C / min) in an argon atmosphere in a tube furnace for 4 h, and cool it naturally to room temperature to obtain coral-like Nb2O5@C.
[0088] The test showed that the first discharge specific capacity of the sample at a current density of 0.25C was 180 mAh / g.
[0089] Example 5 (Nb2O5@C)
[0090] Niobium pentachloride and sodium alginate are used as initial raw materials.
[0091] First, 0.65 g of niobium pentachloride was weighed and dispersed in 20 mL of ethylene glycol and 40 mL of water, transferred to a 100 mL reactor, and reacted at 200 ° C for 20 hours. The product obtained after hydrothermal treatment was centrifuged and washed three times with water and ethanol, respectively, at a centrifugal speed of 6000 rpm, each centrifugal time of 5 minutes, and then dried in a vacuum drying oven at 80 ° C for 8 hours to obtain Nb2O5 powder.
[0092] 150 mg of sodium alginate was weighed and dissolved in 80 mL of water, and 55 mg of Nb2O5 powder was weighed and added to the sodium alginate solution, and stirred at room temperature for 9 h to obtain a precursor. The precursor was annealed at 800 ° C (heating rate of 10 ° C / min) for 6 h in an argon atmosphere in a tube furnace, and naturally cooled to room temperature to obtain coral-like Nb2O5@C.
[0093] After testing, the first discharge specific capacity of the sample at a current density of 0.25C is 174mAh / g.
[0094] Example 6 (Nb2O5@C)
[0095] Hydrated niobium oxalate and glucose are used as initial raw materials.
[0096] First, 60 mL of ethylene glycol and 20 mL of water were mixed, 0.96 g of hydrated niobium oxalate was weighed and dispersed in the mixture, magnetically stirred for 40 min, and then ammonium hydroxide was added to adjust the pH to neutral, and then transferred to a 100 mL reactor and reacted at 180 ° C for 18 h. The obtained product was centrifuged and washed three times with water and ethanol, respectively, at a centrifugal speed of 5500 rpm, and each centrifugal time was 5 minutes, and then vacuum dried at 80 ° C for 10 h to obtain Nb2O5 powder.
[0097] 1.43g glucose was weighed and dissolved in 50mL water, 0.53g Nb2O5 powder was dispersed in the glucose solution, and magnetic stirring was performed at room temperature for 6.5h to obtain the glucose-coated niobium pentoxide precursor. The precursor was annealed at 660℃ (heating rate of 5℃ / min) in an argon atmosphere in a tube furnace for 7h, and naturally cooled to room temperature to obtain flower-shaped Nb2O5@C.
[0098] After testing, the first discharge specific capacity of the sample at a current density of 0.25C is 193mAh / g.
[0099] Comparative Example 1
[0100] A Nb2O5 nanosheet is used as a negative electrode material for sodium ion capacitors. The synthesis method of the material is to use niobium foil, hydrofluoric acid (HF), and lithium hydroxide (LiOH) as precursors to in-situ hydrothermal synthesize the Nb2O5 nanosheet. The final Nb2O5 nanosheet shows a high conductivity at 50 mAg -1 170mAh g -1 The initial discharge capacity.
[0101] Example 7 (Electrochemical Performance Test)
[0102] The Nb2O5@C obtained in Examples 1-6 and Comparative Example 1 was mixed with the conductive carbon black and the binder PVDF in a mass ratio of 7:2:1 to prepare a 1.5 mg / cm 2The positive electrode sheet was matched with the sodium sheet as the negative electrode, and the electrolyte with NaClO4 as the solute, ethylene carbonate (EC) and dimethyl carbonate (DMC) (EC:DMC=1:1vol%) as the solvent and 5% fluoroethylene carbonate (FEC) as the additive was used. The Nb2O5@C half-cell was assembled in the order of positive electrode shell / electrode sheet / polypropylene diaphragm / sodium sheet / gasket / negative electrode shell, and the electrochemical properties of Nb2O5@C were tested.
[0103] The electrochemical performance of Nb2O5@C was obtained by constant current charge and discharge test of the above Nb2O5@C half-cell:
[0104] The first discharge specific capacity of Nb2O5@C prepared in Example 1 at a current density of 0.25C is 245 mAh / g.
[0105] The first discharge specific capacity of Nb2O5@C prepared in Example 2 at a current density of 0.25C is 192 mAh / g.
[0106] The first discharge specific capacity of Nb2O5@C prepared in Example 3 at a current density of 0.25C is 175 mAh / g.
[0107] The first discharge specific capacity of Nb2O5@C prepared in Example 4 at a current density of 0.25C is 180 mAh / g.
[0108] The first discharge specific capacity of Nb2O5@C prepared in Example 5 at a current density of 0.25C is 174 mAh / g.
[0109] The first discharge specific capacity of Nb2O5@C prepared in Example 6 at a current density of 0.25C is 193 mAh / g.
[0110] The Nb2O5 of Comparative Example 1 was -1 The first discharge specific capacity at a current density of is 170 mAh / g.
[0111] By comparing the first discharge specific capacity of Nb2O5@C prepared in Examples 1-6 and the Nb2O5 of the comparative example, it can be seen that the specific capacity of Nb2O5@C prepared by the method of the present invention is significantly greater than the specific capacity of Nb2O5 of the comparative example, indicating that the Nb2O5@C prepared by the present invention has excellent electrochemical performance.
[0112] Example 8 (Sodium Ion Microcapacitor)
[0113] The Nb2O5@C prepared in Example 1 was used as the negative electrode, activated carbon (AC) as the positive electrode, and highly conductive electrochemically exfoliated graphene (EG) nanosheets as the current collector and conductive additive, and planar interdigitated Nb2O5@C / / AC-NIMSCs were prepared by mask filtration method.
[0114] Due to the high capacity and fast charging characteristics of Nb2O5@C, Nb2O5@C / / AC-NIMSCs have a high charge capacity of 60.7 μWh / cm 2 High surface energy density and excellent long cycle performance (at 300μA / cm 2 After 8000 cycles at the same current density, the capacitance retention rate was 75%).
[0115] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A Nb2O5@C material, characterized in that: The Nb2O5@C is formed by combining niobium pentoxide material and carbon material; the Nb2O5@C material has a three-dimensional porous structure; The microscopic morphology of the Nb2O5@C material is in the shape of a flower cluster, and a single three-dimensional flower-like structure is composed of multiple cross-layered nanosheets; The carbon material is coated on the surface of the nanosheet.
2. A Nb2O5@C material according to claim 1, characterized in that: The particle size of the single three-dimensional flower-shaped structure is 1 to 5 μm; the thickness of the nanosheet is 10 to 50 nm; and the thickness of the coated carbon layer is 2 to 4 μm.
3. A method for preparing a Nb2O5@C material according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: S1: a solution I containing a niobium source is heated under closed conditions to react I to obtain an intermediate I; S2: mixing the intermediate I in step S1 with a carbon source to obtain an intermediate II; S3: After the intermediate II in step S2 is subjected to heat treatment II in an inactive atmosphere, the Nb2O5@C material is obtained.
4. The method for preparing a Nb2O5@C material according to claim 3, characterized in that: In step S1, the niobium source and the solvent are mixed and stirred for 0.5 to 2 hours to obtain the solution I, and the pH of the solution I is neutral; Preferably, in step S1, the temperature of the heating reaction I is 150-200° C., and the time of the heating reaction I is 20-24 h.
5. The method for preparing Nb2O5@C material according to claim 3, characterized in that: In step S2, the intermediate I is mixed with a carbon source and stirred for 5 to 10 hours to obtain an intermediate II; Preferably, in step S3, the temperature of the heat treatment II is 500-800° C., and the time of the heat treatment II is 3-10 hours.
6. The method for preparing Nb2O5@C material according to claim 3, characterized in that: The niobium source is selected from hydrated niobium oxalate or niobium chloride; Preferably, the carbon source is selected from dopamine, glucose or sodium alginate; Preferably, the molar ratio of the niobium source to the carbon source is 0.8-1.2:0.8-1.2; wherein the molar number of the niobium source is calculated based on the molar number of niobium element in the niobium source, and the molar number of the carbon source is calculated based on the molar number of carbon element in the carbon source.
7. The method for preparing Nb2O5@C material according to claim 4, characterized in that: In step S1, the solvent is a mixture of water and ethylene glycol in a volume ratio of 1 to 3; Preferably, in step S3, the inert atmosphere is selected from nitrogen and / or argon.
8. Use of the Nb2O5@C material according to claim 1 or 2 as a negative electrode material in a sodium ion microcapacitor.
9. A negative electrode material for a sodium ion microcapacitor, characterized in that: The negative electrode material comprises a Nb2O5@C material as claimed in claim 1 or 2; wherein the content of Nb2O5@C in the negative electrode material is 50 to 90 wt%.
10. A sodium ion microcapacitor, characterized in that: The negative electrode material of the sodium ion micro-capacitor includes the negative electrode material of the sodium ion micro-capacitor according to claim 9.